Mitigating Gharar and Dharar in Digital Cosmetic Advertising: A Sharia Marketing Perspective on Influencer Endorsements - Ahsana, Elsa Amelia; Ninik Azizah (Tebuireng: Journal of Islamic Studies and Society, 2026)
This study investigates the aggressive digital marketing strategies utilized by contemporary cosmetic brands to capture evolving consumer demographics. Specifically, the research aims to examine the mechanisms of influencer branding deployed by Glad2Glow on digital platforms and analyze these promotional methods through the conceptual lens of Sharia Marketing to establish ethical-legal boundaries for modern digital commerce. Methodologically, this study adopts a normative juridical research design integrated with conceptual and phenomenological approaches. Data collection was systematically conducted through an extensive literature review, analysis of formal Islamic jurisprudence materials, and structural social media monitoring on TikTok, focusing on both primary and secondary qualitative legal-ethical sources. The empirical findings reveal that Glad2Glow’s partnership with prominent beauty influencers successfully cultivates deep consumer trust and strong emotional attachments through a distinct combination of radical honesty and multi-day user-progress storytelling. From a Sharia Marketing viewpoint, this branding framework satisfies the core pillars of Akhlaqiyyah (ethics) and Al-Waqi’iyyah (realism) by effectively mitigating informational asymmetry (tadlis) and commercial overclaiming (gharar). However, critical vulnerabilities emerge regarding the Al-Insaniyyah (humanism) and Rabbaniyyah (theism) dimensions, where risks of physical skin irritation (dharar) and age-inappropriate consumer targeting persist due to the highly persuasive nature of viral endorsements. In conclusion, while the strategy successfully drives mass sales conversion, balanced demographic filtering and transparent risk education remain mandatory under Islamic economic frameworks.